Odessa Italian Opera and Eastern War: Features of the Theatrical Season of 1854–1855 - Batsak, Kostiantyn (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2019)
The relevance of the article is to investigate the scenic activities of the Italian troupe, as well as the organizational, financial activities of theatrical enterprise in connection with the sociocultural processes in Odessa within the Eastern war. Main objectives of the article are to study the circumstances and content of the artistic and sociocultural activities of the Italian enterprise in 1854/55 theatrical year. The methodology involves the application of the semiotic method (to study the specificity of the Italian opera influence on the everyday city life), the mosaic reconstruction method (to reproduce the unknown facts influenced the content and nature of the Italian troupe participants’ and its leaders’ activities) and the method of cross-disciplinary analysis (to identify the Italian artists’ scenic activities and the phenomena of socio-political life interconnections). The complex application of designated methods allows to investigate the Odessa Musical Theatre as an integral phenomenon of culture, as well as to define various ways of its interaction with the urban society under the influence of wartime -political events in the Southern region. Results and conclusions. The Italian enterprise of 1854/55, sensitively reacting to the challenges caused by the deployment of the events of the Eastern War not far from Odessa, made adjustments to the established traditions of musical and theatrical activity. Remaining an important centre of artistic life, the Italian opera in that time, due to increased number of opera buffs in the repertoire, became an important instrument of local authorities helped them to reduce anxious expectations and overcome the panic of the population after the bombing of the city. The presence throughout the theatre season of a large number of medium officer stuff representatives in the parterre audience determined their influence on the audience genre preferences, also facilitated increasing a number of "mass" audience and levelling the requirements for the artists’ qualities. The financial crisis in the theatre, caused by the city budget deficit escalated within the hostilities, determined the opera company foreign engagement cost reduction, which led to engaged singers’ performing quality deterioration.